Snow in Summer: Poetic Teachings from Cottonwood and Ponderosa - Beavington, Lee (Art/Research International)

(untitled) (University of Alberta, 2022)
In this article, art is used as inquiry to ask powerful questions, untangle paradoxes, and help us navigate loss and grief in the Anthropocene. Several central questions are considered and animated through narrative and poetry. How do we live poetically (Leggo, 2005) in a world that we need to exploit in order to survive? How do we engage in a more-than-human world full of ambiguity and paradox? How might nature become a teacher or mentor (Jickling et al., 2018), and what anthropocentric barriers do we face? How can stories and poems facilitate holistic expression and place-based connection? As we elucidate the wonder and loss of cottonwood, and the mentorship of ponderosa, Carl Leggo (2004, 2005, 2012, 2016, 2019a, 2019b) serves as a guide for artful attending and hopeful imagination for living poetically. Joanna Macy’s (Macy & Johnstone, 2012; Macy & Brown, 2014) work that reconnects and Leggo’s curriculum of joy offer parallel paths of grief and hope so that we might find our way through the Anthropocene.